2023
DOI: 10.47197/retos.v48.96283
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre calidad del sueño, hábitos alimentarios y perfil antropométrico en adolescentes: Una en-cuesta transversal (Relationship between sleep quality, eating habits, and anthropometric profile in adolescents: A cross-sectional survey)

Abstract: La obesidad representa un importante factor de riesgo para diversas enfermedades no transmisibles (ENT) en los adolescentes y la población general. El propósito de este estudio fue determinar la relación entre la calidad de sueño, hábitos alimentarios y perfil antropométrico en adolescentes peruanos. Se llevó a cabo un estudio transversal. Un total de 240 adolescentes de edades comprendidas entre 12 a 17 años participaron en el estudio. Se utilizó el Cuestionario de Calidad del Sueño de Pittsburgh (PSQI) y un … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…In the present study, we found that participants who were 16 or older tended to report MetS; furthermore, an age ≥ 16 years was significantly associated with MetS. These findings are similar to the results reported in a recent study conducted in Peruvian adolescents where the highest proportion of those with MetS, measured by WHtR, were aged 15 to 17 years vs. 12 to 14 years ( 4 ). In addition, these results confirm the findings of research that measured waist circumference and WHtR in US children and adolescents ( 48 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, we found that participants who were 16 or older tended to report MetS; furthermore, an age ≥ 16 years was significantly associated with MetS. These findings are similar to the results reported in a recent study conducted in Peruvian adolescents where the highest proportion of those with MetS, measured by WHtR, were aged 15 to 17 years vs. 12 to 14 years ( 4 ). In addition, these results confirm the findings of research that measured waist circumference and WHtR in US children and adolescents ( 48 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have documented the influence of sex and age on the anthropometric profile, more precisely MetS, measured through the WHtR ( 4 , 41–43 ). The results of the logistic regression analysis of the current study revealed that men were more likely to have MetS compared to females; furthermore, we found that a higher proportion of men had MetS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los estudiantes están capacitados para interiorizar la información (Rigney et al, 2021). Por ello, la adquisición de conocimientos en la rama del sueño es determinante para predecir su comportamiento posterior, el cual pueda desembocar en una calidad del sueño adecuada (LeBourgeois et al, 2005;Malque et al, 2023).…”
Section: Discussionunclassified